2010
DOI: 10.1007/s00442-010-1589-1
|View full text |Cite
|
Sign up to set email alerts
|

Ecological engineering by a native leaf-cutting ant increases the performance of exotic plant species

Abstract: Numerous mechanisms are proposed to explain why exotic plants successfully invade natural communities. However, the positive effects of native engineers on exotic plant species have received less consideration. We tested whether the nutrient-rich soil patches created by a native ecological engineer (refuse dumps from the leaf-cutting ant Acromyrmex lobicornis) increase the performance of exotic more than native plants. In a greenhouse experiment, individuals from several native and exotic species were planted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 42 publications
(55 reference statements)
1
24
0
1
Order By: Relevance
“…There are few experimental studies of the effects of refuse dumps on plant performance, and results are conflicting. For example, recent studies showed that refuse dumps consistently increased the growth of exotic plant species, but native plant species showed a more heterogeneous growth response (Farji-Brener & Ghermandi 2004, 2008Farji-Brener et al 2010). Consequently, more experimentation is needed to determine to what extent and how refuse dumps may enhance native plant performance and establishment.…”
Section: Introductionmentioning
confidence: 99%
“…There are few experimental studies of the effects of refuse dumps on plant performance, and results are conflicting. For example, recent studies showed that refuse dumps consistently increased the growth of exotic plant species, but native plant species showed a more heterogeneous growth response (Farji-Brener & Ghermandi 2004, 2008Farji-Brener et al 2010). Consequently, more experimentation is needed to determine to what extent and how refuse dumps may enhance native plant performance and establishment.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Lactuca serriola contains latex, which has been reported to be toxic to most herbivores (Ramos et al 2010). Carduus thoermeri and Onopordon accanthium have relatively high levels of foliar nutrients (Farji-Brener and Ghermandi 2008;Farji-Brener et al 2010), and this could explain their high damage levels reported in this study. Thus, plants in this study have a great variety of defenses, even when six of them belong to the same family.…”
Section: Discussionmentioning
confidence: 58%
“…Specifically, root growth is particularly enhanced in plants growing on refuse materials, leaf‐cutting ant nests and dry habitats. As we showed that refuse materials have higher nutrient content than nest soils, it is reasonable that the roots that access this substrate show greater growth (Farji‐Brener & Ghermandi ; Farji‐Brener, Lescano & Ghermandi ). The huge production of refuse material, high ant density and colossal dimensions of leaf‐cutting ant nests may enhance this process (Farji‐Brener & Werenkraut ).…”
Section: Discussionmentioning
confidence: 81%
“…This positive effect of ant nests on individual plants apparently does not extend to population and community levels. It is known that not all plant species respond equally to the excess of soil resources (Farji‐Brener, Lescano & Ghermandi ). Moreover, the physical characteristics of ant nests and the changes in microclimatic conditions generated by ant activities may act as ecological filters for plant recruitment disfavouring or favouring particular species (Garrettson et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation